THREE USM LECTURERS NAMED MOST CITED RESEARCHERS BY SHANGHAI JIA TONG ACADEMIC RANKING OF WORLD UNIVERSITIES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 30 August 2016 Three Universiti Sains Malaysia (USM) lecturers in various fields of Engineering have made the institution proud when they were listed amongst the "Most Cited Researchers" in the recent Shanghai Academic Ranking of World Universities 2016 by subjects.